Expectation-perception gap in Private Higher Education Institutions in Malaysia - Daud S.; Sapuan N.M. (2023)
The issues of quality in Higher Education Institutions (HEIs) in Malaysia are always under public scrutiny, especially for Private Higher Education Institutions (PHEIs). There is little agreement on how the quality is measured. This study examines students' view in relation to their expectation and perception of service quality that they are experiencing in their HEIs. Another purpose of this study is to assess the gap in students' expectations and perceptions towards the quality of service that they had been accorded to from their respective HEIs using the differencing technique. Data was collected using structured questionnaire from 200 students of Business and Management Faculty of the PHEIs. The results showed that PHEIs should improve their ability to perform the promised service dependably and accurately so that they can gain customers' trust. Copyright 2009 Inderscience Enterprises Ltd.